(untitled) (Proceedings OPTIMAL, 2024)
Pregnancy is a condition in which a woman carries and develops a fetus in her womb. This happens when a fertilized egg is attached to the uterine wall by a sperm cell and develops into an embryo. This process usually lasts about nine months, during which the fetus grows and develops into a baby ready to be born. Pregnancy can bring about physical, emotional, and psychological changes in women, and requires special attention to health and nutrition for both mother and fetus. Blood glucose is a carbohydrate in the form of a monosaccharide most commonly found in circulating blood, derived from dietary intake and stored as glycogen in the liver and skeletal muscle. It also refers to the level of glucose present in the blood at any given time. Blood glucose can be generated through the processes of glycogenolysis and glyconeogenesis, where glucose is formed from non-carbohydrate substrates such as fat and protein. HbA1c (Hemoglobin A1c) is a blood test that measures the average amount of blood glucose over a period of about 2-3 months. The type of research used in this study is descriptive research in the form of tables and percentages. This study aims to describe HbA1c blood glucose levels in third trimester pregnant women at RSU Mitra Medika Bandar Klippa. This research was conducted starting from July-August 2024. The samples in this study were third trimester pregnant women as many as 15 samples. The sampling technique used in this study was accidental sampling. The method used in this study, using the Immunofluoresence Analyzer method. From the results of research that has been carried out on 15 samples, it shows that those with normal HbA1c levels are 6 samples (40%) prediabetes HbA1c levels are 5 samples (33.33%) and diabetic HbA1c levels are 4 samples (26.66%).